The Use of Sarcasm in ESP Classes - Mirela COSTELEANU (Scientific Bulletin of the Politehnica University of Timişoara: Transactions on Modern Languages)
Sarcasm can be defined as the use of words that mean the opposite of what the speaker actually says, especially to insult the recipient, to show irritation or to amuse the others. Sarcastic remarks are funny and constructive when they are mutually understood within a genuine relationship. Sarcasm has the potential to catalyze creativity for those who produce and receive it. A positive message delivered in a friendly tone - „You did a great job” and a negative message delivered in a patronizing or deprecating tone - “Your answers are far beyond all expectations” - are congruent.